Cavernous sinus syndrome: need for early diagnosis (2015)
Cavernous sinus syndrome (CSS) is a rare condition characterised by ophthalmoplegia, proptosis, ocular and conjunctival congestion, trigeminal sensory loss and Horner’s syndrome. These signs and symptoms result from the involvement of the cranial nerves passing through the cavernous sinus. We report the case of a 53-year-old man with a history of daily stabbing headache associated with dizziness, progressive blurred vision, right ocular pain, ptosis and ophthalmoplegia. After working up the patient, a meningioma was identified as the cause of the CSS. Despite advances in neuroimaging techniques, in some cases, the aetiology of CSS remains difficult to determine. We highlight the clinical and radiological features of a meningioma, one of the causes of CSS. Early diagnosis and treatment of CSS play a key role in a better prognosis.